Correlation between sectoral GDP and the values of road freight transportation in Colombia - Carlos Felipe Urazán-Bonells; Hugo Alexander Rondón-Quintana; Carlos Alfonso Zafra-Mejía (Economies, 2024)
A correlation between economic development and road freight is demonstrated in the literature review provided in this paper. This relationship was studied in relation to the global gross domestic product (GDP) of the countries under review. Therefore, this paper presents the validation of this correlation in the Colombian case, based not only on global GDP, but also on the GDP for each of the main economic sectors of the country. The correlation was analyzed using several of the following statistical methods: correlation using the non-parametric method (Spearman), the causality relationship using the Granger test, the relationship between variables using Principal Component Analysis (PCA), and multivariate correlation to establish the level of significance of each economic sector by means of the p-value. The study concludes that the best correlation is between the GDP of some economic sectors and the amount of freight transported one year later.
Keywords: 330; cargo transport; Colombia road cargo index; correlation GDP